(untitled) (Jurnal Media Akuakultur Indonesia, 2021)
Intensive fish farming activities mean rearing fish with high stocking densities and providing artificial feed. This will have an impact on poor water quality and the growth of cultivated organisms. This research aims to measure the growth of goldfish and Taiwanese kijing that are reared in polyculture. The research used a Completely Randomized Design (CRD) consisting of stocking density of carp (C. carpio) 30 individuals and initial weight (20 gr) then stocking density of Taiwan kijing (A. woodiana) 0, 20, 40, 60 individuals with weight measurements initial 11 gr. The experimental container used was an aquarium with a length of 100 cm x width. The results of the research showed that there was an increase in the body weight of goldfish during different observations for each treatment. And good growth in treatments with high stocking densities, based on the results of analysis of variance, there were significant differences between treatments (P<0.05). For the growth of the Taiwanese kijing, it can be seen that there is an increase in body weight every week, and good growth in the treatment with a lot of fresh density. Based on the results of analysis of variance, there were significant differences between treatments (P<0.05). The conclusion of this research is that there is good growth of goldfish and Taiwanese kijing with high stocking densities.